IKZF3 deficiency potentiates chimeric antigen receptor T cells targeting solid tumors. (1st January 2022) - Zou, Yan; Liu, Bo; Li, Long; Yin, Qinan; Tang, Jiaxing; Jing, Zhengyu; Huang, Xingxu; Zhu, Xuekai; Chi, Tian
Abstract: Chimeric antigen receptor (CAR) T cell therapy has been successful in treating hematological malignancy, but solid tumors remain refractory. Here, we demonstrated that knocking out transcription factor IKZF3 in HER2-specific CAR T cells targeting breast cancer cells did not affect CAR expression or CAR T cell differentiation, but markedly enhanced killing of the cancer cells in vitro and in a xenograft model, which was associated with increased T cell activation and proliferation. Furthermore, IKZF3 KO had similar effects on the CD133-specific CAR T cells targeting glioblastoma cells. AlphaLISA and RNA-seq analyses indicate that IKZF3 KO increased the expression of genes involved in cytokine signaling, chemotaxis and cytotoxicity. Our results suggest a general strategy for enhancing CAR T efficacy on solid tumors. Highlights: CAR-T cells are hardly effective against solid tumors. CRISPR was used to delete the transcription factor IKZF3 from HER2-specific CAR T cells targeting human breast cancer. IKZF3 KO potentiated killing of the breast cancer cells due to increased cytokine signaling, chemotaxis and cytotoxicity. Similar effects were seen when IKZF3 was deleted in CD133-specific CAR T cells targeting glioblastoma cells. These data suggest a general strategy for improving solid tumor immunotherapy.